Post purchase behavior on marketing mix in meeting customers satisfaction on MyVi car / Noor Hardhilah Abdul Hadi - Abdul Hadi, Noor Hardhilah (Faculty of Business and Management, 2006)
In this modern day business environment, the business world is getting more competitive and aggressive by day to day. In order to stay in business in an era of high competition one must manage the service quality and able to give better offer rather than others for the purpose of attracting the customers. The customer is satisfied and delighted if the products and services performance matches their expectations. Therefore, the aim of this research is to identify level of customer satisfaction. This includes to identify the factors that influence level of customer satisfaction on MyVi cars and to examine the relationship between marketing mix (customer service, product, price, promotion and place) and level of satisfaction. This paper consists of 5 chapters which explain the subject matter in the stage. Chapter 1 explains the introduction and background of the study. Chapter 2 explains the literature review, which relates to the subject studied and theoretical framework which act as a guide to the research flow and process. For Chapter 3, research methodology is explained, which consist of methods and sampling techniques be used. Data findings and discussions is explained in Chapter 4, derived from the information obtain from respondents. Finally, Chapter 5 contain summary of results and findings, which explain conclusion and recommendations. From the findings, the conclusion can be made whether customers are satisfied with the MyVi cars.